Development Male Students’ Skills in Solving HOTS Problem in Terms of Self Confidence - Andreansyah, Mohamad; Aini, Afifah Nur (Insitut Agama Islam Negeri Kerinci, 2023)
Higher Order Thinking Skills (HOTS) type math problems are one way to develop students' higher order thinking skills. One aspect that affects problem solving ability is self confidence. Therefore, this study will describe the development of students' problem solving skills in terms of self confidence. This research is descriptive qualitative type with six male students as the subjects. At the initial stage, a questionnaire was given to determine the level of students' self-confidence. Then two subjects at each level were selected to take the problem solving ability test. As a triangulation, semi-structured interviews were conducted. The test and interview results were analyzed using the Miles and Hubberman model by adjusting to the problem solving steps, namely: understanding the problem, determining the solution plan, implementing the solution plan, and checking back. The results showed that subjects with high self confidence were able to develop problem solving skills, subjects with moderate self confidence only fulfilled the steps of understanding the problem and developing a solution plan, while subjects with low self confidence were only able to understand the problem. Thus, students with self confidence are better at developing problem solving skills, so it is important for educators to help students develop their self confidence through appropriate teaching methods, such as providing constructive feedback and providing opportunities for students to actively participate in the teaching and learning process.